2008
DOI: 10.1037/0033-2909.134.3.460
|View full text |Cite
|
Sign up to set email alerts
|

The role of the media in body image concerns among women: A meta-analysis of experimental and correlational studies.

Abstract: Research suggests that exposure to mass media depicting the thin-ideal body may be linked to body image disturbance in women. This meta-analysis examined experimental and correlational studies testing the links between media exposure to women's body dissatisfaction, internalization of the thin ideal, and eating behaviors and beliefs with a sample of 77 studies that yielded 141 effect sizes. The mean effect sizes were small to moderate (ds = -.28, -.39, and -.30, respectively). Effects for some outcome variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

60
1,035
10
61

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,510 publications
(1,224 citation statements)
references
References 162 publications
(145 reference statements)
60
1,035
10
61
Order By: Relevance
“…Thus, disclaimer labels may be powerless to tackle social comparison for women high on trait appearance comparison. As previous research has shown that the negative effects from thin ideal exposure happen particularly for women who have internalised the thin ideal to a greater extent (Dittmar & Howard, 2004;Grabe et al, 2008;Groesz et al, 2002), intervention efforts might be more effective if focussed on preventing internalisation of the thin ideal, rather than trying to reduce appearance comparison after the fact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, disclaimer labels may be powerless to tackle social comparison for women high on trait appearance comparison. As previous research has shown that the negative effects from thin ideal exposure happen particularly for women who have internalised the thin ideal to a greater extent (Dittmar & Howard, 2004;Grabe et al, 2008;Groesz et al, 2002), intervention efforts might be more effective if focussed on preventing internalisation of the thin ideal, rather than trying to reduce appearance comparison after the fact.…”
Section: Discussionmentioning
confidence: 99%
“…It has now been well established that exposure to thin idealised media images can impact negatively on women's body image (Grabe, Ward, & Hyde, 2008;Groesz, Levine, & Murnen, 2002;Levine & Murnen, 2009;Want, 2009). These negative effects happen particularly for more vulnerable women, that is, for those who have internalised the thin ideal to a greater extent (Dittmar & Howard, 2004;Grabe et al, 2008;Groesz et al, 2002;Heinberg & Thompson, 1995;Yamamiya, Cash, Melnyk, Posavac, & Posavac, 2005) or for whom appearance is important to their self-concept (Dittmar & Howard, 2004;Halliwell & Dittmar, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mass media's portrayal of an ultrathin physique for women and a lean-muscular physique (i.e., musculature coupled with low body fat) for men is though to be behind body discontent and eating pathology [16][17][18][19][20]. Despite accumulated evidence of the effects of acute exposure to media-idealized images on viewers' negative body-feelings and ED symptoms [16,[19][20][21], the degree to which body image and eating related disturbances are culturally bound issues, [22], linked to, and caused by media's portrayal of gendered beauty ideals continues to be an issue of debate see [19,[23][24][25].…”
mentioning
confidence: 99%
“…For example, neuroscientists find that among humans, faces of higher social status individuals incite more gazing attention than those of lower status people (Dalmaso et al, 2012). Research on fashion diffusion also suggests that new styles first adopted by higher status elites gradually diffuse to lower status people through imitation (Grabe et al, 2008;Simmel, [1904Simmel, [ :1957). …”
Section: Higher-status Preferencementioning
confidence: 99%